The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1321103x16642631
|View full text |Cite
|
Sign up to set email alerts
|

Music in the early years: Pathways into the social world

Abstract: Two assumptions that underlie much research in early childhood music education are that music is a social endeavor and musical participation is beneficial to children's overall social development. As members of cultural and social groups, young children engage with music in a multitude of ways and with different companions. This article examines young children's musical engagement from a social perspective, integrating research from a wide range of fields and theoretical orientations. The first section brings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 74 publications
(129 reference statements)
4
33
0
4
Order By: Relevance
“…Previous studies have suggested that music activities enhance children’s sociability (as reviewed in Ilari, 2016 ). Even for infants, musical activities can enhance social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that music activities enhance children’s sociability (as reviewed in Ilari, 2016 ). Even for infants, musical activities can enhance social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Although professional interest in the musical activity of young children from a broader perspective than that of the school is increasing and different researchers have broadened the framework of understanding to encompass the home, family and recreation spaces (Welch, 2005a;Barrett, 2009Barrett, , 2012Trevarthen & Malloch, 2012;Ilari, & Habibi, 2015;Ilari, 2016), this research is still rather limited, perhaps due to the 'difficulties in accessing the intimate private worlds of children and their families' (Barrett, 2009, p. 116), with most research focusing on somewhat older young people (Green, 2001;Lamont et al, 2003).…”
Section: Musical Experience and Its Implications For Building Identitymentioning
confidence: 99%
“…Throughout history, music has been an important aspect of human life (Wright & Rubin, 2016). Starting at birth people are exposed to various forms of music, and sometimes go as far as creating their own music during early stages of life (Ilari, 2016). Essentially, as humans, we are born with an appreciation for music and it continues to be a source of enjoyment throughout people's lives.…”
Section: Introductionmentioning
confidence: 99%